DAMPAK PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN DI PERUSAHAAN PERBANKAN - Faizal Rizky Yuttama; Slamet Slamet (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
The country's unstable economic condition due to the COVID-19 pandemic has a major impact on economic growth. The condition of the company is experiencing liquidity pressure which can result in default. This study is a quantitative study to determine the effect of financial performance in banking companies. This study uses a sample of commercial banks listed on the Indonesia Stock Exchange (IDX) before the COVID-19 pandemic occurred in the 2019 quarter period and the COVID-19 pandemic period in the 2020 quarter. The sampling technique used purposive sampling with certain criteria. The analysis technique using regression analysis was carried out with the classical assumption test. Based on the results of the analysis found that TPF has a positive and significant effect on Return on Assets (ROA), NPL has a negative and significant effect on Return on Assets (ROA), LDR has a positive effect on Return on Assets (ROA), CAR has a positive effect on Return on Assets ( ROA), and NIM have a positive and significant effect on Return on Assets (ROA). The contribution of this research is to determine the impact of the COVID-19 pandemic on the banking industry, which serves as an intermediary function between recipients and distributors of fundsKeyword : CAR, DPK, NIM, NPL, Covid-19 Pandemic, ROA